(untitled) (Fiep Bulletin - online, 2015)
In the current days, a considerable increase has been verifying in the discussions on the methodologies of teaching of the collective Sporting games, with countless subjects in debate, mainly in the pedagogic approaches used with children and young, what causes a lot of times the teachers and technicians if they see " in a street without exit " (Bayer, 1986, p.8). In this sense, the objective of this work was to accomplish a historical report of the main Methodologies of teaching of the Collective Sporting Games adopted in Brazil, the principal percussionists of these methodologies, as well as to point the main advantages and disadvantages of your use in the process of teaching-learning-training of the Collective Sporting Games. For so much, he/she took place a bibliographical research, where the results presented to coexist two pedagogic currents of teaching for the collective Sporting games: one uses the methods traditional or didactic, that decompose the elements (fragmentation) constituent of the game and the other current detaches the active methods, that take into account the youths’ interests and that, starting from lived situations, initiative, imagination and reflection can favor the acquisition of a knowledge adapted to the situations caused by the unpredictability. Among those two pedagogic currents, they stand out several Methodologies of teaching of the Collective Sporting Games, which we will detach the more used in the process of teaching-learning-training of the Collective Sporting Games. It is ended that the presented methods present so much advantages, as disadvantages, but that fundamentally method doesn’t totally exist mistaken, or be the misunderstanding a lot of times it is the moment of use, the place and for who the method will be used, however it is noticed the need, mainly in the schools, where habitually the teaching of the Collective Sporting Games has been an exclusive practice of the " talented " ones, the use of the active methods, that take into account the youths’ interests and that, starting from lived situations, initiative, imagination and reflection can favor the acquisition of a knowledge adapted to the situations caused by the unpredictability.